FENOMENA SOCIAL CLIMBER PADA MAHASISWA DI KOTA PEKANBARU - Erviandy Setia Dharma; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is motivated by a phenomenon that is happening among students, the behavior of student social climber is very prevalent in increasingly modern times. Social climber behavior is a person who seeks an recognition of their status and a higher social status than the actual status. Thus students can create or increase their social status. This research was conducted to determine the motives, meanings and communication experiences of Social climber Students in Pekanbaru City. The purpose of this study was to determine the Social climber Phenomenon of Students in Pekanbaru City which can be seen from the motives, meanings and communication experiences of social climber students.This research method uses a qualitative descriptive method. The subjects of this study were social climber students in Pekanbaru City. While the object of this research is a point of attention of a study, namely regarding the phenomenon of social climber in students in the city of Pekanbaru by identifying the motive, meaning and experience of communication. The data collection techniques used were interviews, observation and documentation. The data analysis technique used an interactive data analysis model. In achieving the validity of the data in this study, the authors used participation extension and triangulation.The results showed that the social climber students in the city of Pekanbaru had social climber students' motives in the form of past motives (wanting to be rich and influencing the social environment) and future motives (wanting to be considered rich people to get social status recognition). The meaning of social climber for students is popularity and luxury lifestyle. The communication experience of a social climber student is a pleasant communication experience (after becoming a social climber, i.e. more friends and inner satisfaction) and an unpleasant communication experience (before becoming a social climber, which is getting ridicule from others and after becoming a social climber, i.e. getting ridicule from others, negative comments on social media and conflicts with friends).Keywords :Fenomena, Mahasiswa , Social climber.